Reflections on Empiricism and on the Significance of the General Research into Culture - Stoškus, Krescencijus Antanas (Problemos, 1988)
The article continues the discussion initiated already in 1983 in periodical press and deals with some deficiencies of the Lithuanian culture (the tendencies of blind following, provinciality, one-sidedness, enlightened one-purposefulness from top to bottom, etc.). The importance of the discussion has not been appreciated as yet. However, it has convincingly showed that: 1) no empirical description can create the general understanding of the Lithuanian culture, nor can it serve as a sufficient basis for the discussion of today’s culture; 2) the deficiencies of the development and preservation of cultural values, including theoretical ones, can be correctly explained only on the basis of the general research into the Lithuanian culture. The author of the article tries to prove that general theoretical investigations not only make it possible to explain the role and the significance of the particular cultural spheres in the general process of culture but all together should form the general cultural horizon. The latter on its tum must serve as a basis for the ever coming the particularly dangerous proliferation of the professional purblindness, which in the name of the professional interests threatens to destroy the fundamental cultural values and culture in general.